Concentration anomaly of heat capacity in PbTe based solid solutions - Rogacheva, E.I.; Sinelnik, N.A.; Krivulkin, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The temperature dependences of the heat capacity in the Pb₁-xMnxTe and Pb₁-xGexTe (x = 0-0.04) solid solutions based on PbTe were obtained in the temperature range of 100-670 K. Pronounced peaks were observed in the isotherms of the heat capacity in the vicinity of x ~ 0.01-0.015. The presence of the peaks is explained on the basis of the idea about the existence of concentration phase transitions of percolation type, which take place in any solid solution and are related to transformation of impurity discontinuum into impurity continuum.